Impact of 1% chlorhexidine gluconate bathing and emollient application on bacterial pathogen colonization dynamics in hospitalized preterm neonates – A pilot clinical trial. (July 2021) - Dramowski, Angela; Pillay, Sheylyn; Bekker, Adrie; Abrahams, Ilhaam; Cotton, Mark F.; Coffin, Susan E.; Whitelaw, Andrew C.
Abstract: Background: Chlorhexidine gluconate (CHG) body washes and emollient application may modulate bacterial pathogen colonization and prevent neonatal hospital-acquired infections. Methods: This pilot, non-randomized, open-label trial, enrolled preterm neonates (1000-1500g; day 1-3 of life) at a tertiary hospital in Cape Town, South Africa. Participants were sequentially allocated to 4 trial arms (n=20 each): 1% aqueous CHG (CHG), 1% CHG plus emollient (CHG+EM), emollient only (EM) and standard of care (SOC: no antiseptic/emollient). Trial treatment/s were applied daily for 10 days (d) post-enrolment, documenting neonatal skin condition score. Anterior nose, neck, umbilical and perianal swabs for bacterial culture were collected at d1, d3, d10 and d16 post-enrolment, (±1 day), reporting pathogen acquisition rates and semi-quantitative bacterial colony counts. (ClinicalTrials.gov identifier: NCT03896893; trial status: closed). Findings: Eighty preterm neonates (mean gestational age 30 weeks [SD 2]) were enrolled between 4 March and 26 August 2019. The bacterial pathogen acquisition rate (comparing d1 and d16 swabs) varied from 33·9% [95%CI 22·9-47·0] at the umbilicus, 39·3% [95%CI 27·6-52·4] at the neck, to 71·4% [95%CI 58·5-81·7] at both the nose and perianal region. At d10, CHG babies had reduced bacterial density detected from neck, umbilicus, and perianal swabs compared to other groups (see Table 3). Following intervention cessation, colonization density was similar across all trial arms, but S. aureus colonization was more prevalent among EM and CHG+EM babies. Neonatal skin condition score improved in babies receiving emollient application (EM: -0·87 [95%CI 0·69-1·06] and CHG+EM: -0·73 [0·45-0·99]), compared to the SOC and CHG arms (Table 2); no CHG-related skin reactions occurred. Interpretation: Bacterial colonization density was significantly reduced in babies receiving 1% CHG washes but colonization levels rebounded rapidly post-intervention. Emollient application improved skin condition but was associated with higher rates of S. aureus colonization. Funding: South African Medical Research Council; National Institutes of Health (TW010682).